A rapid cotton swab for on-site screening of coloring curcumin on durian skin: food safety aspects - Teerasong S. (2023)
Exported durians from Thailand are sometimes immersed in curcumin to give the fruits a good appearance. Curcumin is regarded as non-toxic additive, however some importing countries prohibited use of any additive to fresh fruits and vegetables. This work aims to develop a rapid, low cost and convenient cotton swab device for curcumin detection. The detection principle involves a colorimetric acid–base characteristic of curcumin. Curcumin in an acidic/neutral solution presents a bright yellow color, while it displays an intense orange–red color in basic solution. A cotton swab acted for both sample collection and as a sensing platform. A pre-moistened swab was used to wipe a durian surface. Afterward, a NaOH solution was dropped onto the swab. A distinct orange–red color appearing on the swab indicates the presence of curcumin. The cotton swab was applied for qualitative analysis of curcumin contaminated on durian husks via visual detection. The developed device provided good reliability, 93.75% (36 samples). Furthermore, the device was demonstrated for quantitative determination using camera detection. Two linear calibrations were obtained in ranges of 10–75 and 75–250 mg L−1, with a detection limit of 3.2 mg L−1. The method was also successfully applied to quantification of curcumin in durians (three samples) and dietary supplements (two samples). The test can be done in a few minutes. The developed device was established as an useful tool for food safety and control of contamination by curcumin in an on-site application. Graphical abstract: [Figure not available: see fulltext.].